Dragon fruit peel waste improves gut barrier integrity and microbiota composition in rats fed a high-fat, high-fructose diet - Chumroenvidhayakul, Siriwan; Thilavech, Thavaree; Abeywardena, Mahinda; Wang, Yanan; Kamonsuwan, Kritmongkhon; Muhlhausler, Beverly; Adisakwattana, Sirichai (My University, 2026)
AbstractA Western-style diet high in fat and fructose has been linked to intestinal barrier dysfunction and gut microbiota dysbiosis. This study aimed to investigate the effects of dragon fruit peel powder (DFP), a by-product rich in dietary fiber and phytochemicals, on fecal characteristics, short-chain fatty acid (SCFA) production, cecal microbial composition, and intestinal barrier function in rats fed a high-fat, high-fructose (HFHFr) diet. Thirty-two male Sprague-Dawley rats were assigned to four groups: control, control + 5 % DFP, HFHFr, and HFHFr + 5 % DFP for 12 weeks. DFP supplementation increased fecal moisture and lipid excretion while reducing fecal pH. In HFHFr-fed rats, DFP mitigated gut barrier impairment and suppressed the metabolic endotoxemia by upregulating tight-junction gene expression and reducing TLR4 expression, and serum lipopolysaccharide-binding protein (LBP) levels. Furthermore, DFP modulated the gut microbiota by increasing the Firmicutes-to-Bacteroidetes ratio, enriching beneficial SCFA-producing genera, and suppressing potentially pathogenic taxa. These microbial shifts were accompanied by a significant increase in cecal SCFA concentrations. These findings indicate that DFP supplementation improves gut barrier integrity markers and beneficially modulates the gut microbiota in HFHFr-fed rats, highlighting its potential as a sustainable functional ingredient to support gastrointestinal health.
Keywords: Dietary fiber; Dragon fruit peel waste; Gut microbiota; High-fat high-fructose diet; Intestinal barrier; short-chain fatty acids